The factors that influence audit quality by earnings surprise benchmark - Vina Aqmarina; Reni Yendrawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study is aimed at analyzing the influence of audit tenure, auditor rotation and age of publication on audit quality. Audit quality is gauged by earnings surprise benchmark. The population in this study is all of manufacturing companies listed on the Indonesia Stock Exchange in the period 2014–2017. Purposive sampling method was employed in this research study to gain the research sample. Then the technique of logistic regression was employed for data analysis. The research findings reveal that audit tenure and auditor rotation have a positive effect on audit quality, while age of publication has a negative effect on audit quality. The implication of this study is that financial statements users should not only focus on high or low profits, but also assess the quality of the audited financial statement.